Metropolitan communities trade guilds, identity, and change in early modern London - Ward, Joseph P. (Stanford Univ. Press, 1997)
The author offers an alternative to this view of London's expansion. His argument begins with an analysis of sermons, tracts, and poems suggesting that some Londoners of the time considered the suburbs subject to the same kinds of authority as the City, which consequently made them integral parts of the metropolis. The author then draws on the records of more than twenty guilds to demonstrate that many members lived and worked in the suburbs and were as capable of flaunting City traditions and authority as immigrants; trade guilds, therefore, were metropolitan by nature. The author argues that guilds, as principal sites for the collision of tradition and innovation, generally took a flexible approach to change rather than simply trying to prevent it